Computational study of the effect of grain boundary and nano-porosity on xenon behavior in UO2 - Zamzamian, Seyed Mehrdad; Kowsar, Zahra; Zolfaghari, Ahmadreza (Journal of applied physics, 2022)
Since xenon (Xe) production is always an unavoidable part of the fission products in fuel pellets, the challenges of its presence have always been the subject of many papers. In line with these goals, in the present paper, the effect of the presence of grain boundaries (GBs) with misorientations ( θ G B) of 36 °, 39 °, 52 °, 53 °, 71 °, and 129 ° in 10%Xe-UO2 (uranium dioxide in which 10% of its uranium atoms have been replaced by xenon atoms) on the behavior of xenon (diffusion, nucleation, and formation of clusters) was investigated by performing molecular dynamics (MD) simulations. The results showed that xenon atoms aggregate in the GB with misorientations of 36 ° and 53 ° and form larger clusters relative to other GBs. This was interpreted due to the low formation energy of these two GBs in comparison with other misorientations. A decrease in the number of xenon atoms was also observed at a slight distance from these two GB regions, indicating their sink efficiency. The calculation of diffusion coefficients also indicated that the presence of these two GBs increases the coefficients (xenon, oxygen, and uranium). All of these demonstrate the effective role of θ G B = 36 ° and θ G B = 53 ° in swelling. To reduce the destructive effect of xenon atoms on the fuel pellet, a conceptual design in the form of nanoporous was proposed. The results of the MD simulation of such a design showed that the presence of nano-porosity significantly reduces xenon clusters.